The Impact of Transcatheter Aortic Valve Implantation (TAVI) on Serum Apelin Levels in Patients with Aortic Valvular Stenosis - Mehmet Kucukosmanoglu; Seyda Sahin; Orsan Deniz Urgun; Arafat Yildirim; Salih Kilic; Omer Sen; Ibrahim Halil Kurt (Brazilian Journal of Cardiovascular Surgery, 2020)
Abstract Introduction: In this study, we aimed to investigate the impact of transcatheter aortic valve implantation (TAVI) on serum apelin levels in patients with severe symptomatic aortic valve stenosis (AS). Methods: Forty-six consecutive patients (76.9±7.4 years, n=27 women) who underwent TAVI and 45 age- and sex-matched control subjects were included in the study. Echocardiographic parameters, serum apelin, pro-brain natriuretic peptide (Pro-BNP), and troponin I levels were compared between the groups. In addition, the preprocedural and first-month follow-up echocardiographic parameters and serum apelin values of TAVI patients were compared. Results: Serum median troponin I and Pro-BNP levels were significantly higher and serum apelin levels were significantly lower in TAVI patients before TAVI procedure than in the control subjects (P<0.001, for all). Median troponin I and Pro-BNP levels were significantly decreased and apelin levels were significantly increased after TAVI procedure compared to the peri-procedural levels. There was a significant and moderate negative correlation between Pro-BNP and apelin levels measured before and after TAVI procedure. A statistically significant and strong negative correlation was found between aortic valve area and Pro-BNP level before TAVI procedure, while a statistically significant but weak positive correlation was found between valve area and apelin level. Conclusion: In our study, apelin levels were significantly lower and Pro-BNP levels were higher in AS patients compared with the control group. Moreover, after TAVI procedure, a significant increase in apelin levels and a significant decrease in Pro-BNP levels were observed. There was also a negative and moderate correlation between apelin and Pro-BNP levels.